Literature Review: The Role Of Motivation And Obstacles In Tourists' Return Visit Intention - Anggia Ayu Lestari; Perengki Susanto; Marwan Marwan; Yunia Wardi; Abror Abror; Vidyarini Dwita (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This article examines the role of tourist motivation, past travel experiences, and perceived barriers in shaping revisit intentions to a destination. This study highlights that revisit intention is influenced by a complex interaction between psychological factors and tourist experiences, not just by service satisfaction alone. The method used is a systematic literature review with a search of articles in the Scopus indexed database. The analyzed studies include empirical and conceptual research relevant to the variables of motivation, experience, barriers, and tourist loyalty. This approach allows for a comprehensive and structured identification of patterns of relationships between variables. The results of the study indicate that intrinsic motivation has a strong contribution to revisit intentions, especially when tourists are driven by emotional experiences and the search for meaning in travel. Past travel experiences play a role in shaping emotional attachments and perceived destination value. Perceived barriers, both physical and psychological, have been shown to reduce tourists' tendency to revisit, although motivational factors and positive experiences can still provide a balancing effect. The interaction of these three variables forms a dynamic decision model in tourist behavior. This study emphasizes the importance of integrating destination management strategies that focus on enhancing tourist experiences, strengthening intrinsic motivation, and reducing travel barriers. This approach is relevant for increasing tourist loyalty and the long-term sustainability of tourist destinations.